Validity of RPP and LKPD based on M-APOS model in clas X senior high school - Shelvia Mandasari; I Made Arnawa; Atmazaki Atmazaki (International Conferences on Educational, Social Sciences and Technology)
RPP and LKPD were an important component an the process of learning, nevertheles in the learning of mathematics. The availablity of RPP and LKPD will help teacher to create interactive, inspiring and fun ways to learn. The M-APOS model was one of the learning model which can trigger students to construct their own knowledge, review on their own and also able to connect all of the knowledge with the subject before. From the case to be underlying to do development RPP and LKPD on M-APOS model. This research is a development research by using Ploomp model that consist of preliminary research, development phase and assesment phase. The purpose of this research is to know the characteristic of RPP dan LKPD with the base of M-APOS model is valid’s criteria. The result of research is RPP and LKPD base of M-APOS model with the average of validity are 0,790 and 0,757.